The Effect of Structured Exercise Compared with Education on Neuropathic Signs and Symptoms in People at Risk of Neuropathic Diabetic Foot Ulcers: A Randomized Clinical Trial - Byron M. Perrin; Jessica Southon; Jane McCaig; Isabelle Skinner; Timothy C. Skinner; Michael I. C. Kingsley (Medicina, 2021)
Background and Objectives: Lifestyle interventions such as exercise prescription and education may play a role in the management of peripheral neuropathy in people with diabetes. The aim of this study was to determine the effect of undertaking an exercise program in comparison with an education program on the signs and symptoms of peripheral neuropathy in people with diabetes at risk of neuropathic foot ulceration. Materials and Methods: Twenty-four adult participants with diabetes and peripheral neuropathy were enrolled in this parallel-group, assessor blinded, randomised clinical trial. Participants were randomly allocated to one of two 8-week lifestyle interventions, exercise or education. The primary outcome measures were the two-part Michigan Neuropathy Screening Instrument (MNSI) and vibratory perception threshold (VPT). Secondary outcome measures included aerobic fitness, balance and lower limb muscular endurance. Results: Participants in both lifestyle interventions significantly improved over time for MNSI clinical signs (MD: −1.04, 95% CI: −1.68 to −0.40), MNSI symptoms (MD: −1.11, 95% CI: −1.89 to −0.33) and VPT (MD: −4.22, 95% CI: −8.04 to −0.40). Although the interaction effects did not reach significance, changes in values from pre to post intervention favoured exercise in comparison to control for MNSI clinical signs (MD −0.42, 95% CI −1.72 to 0.90), MNSI clinical symptoms (MD −0.38, 95% CI −1.96 to 1.2) and VPT (MD −4.22, 95% CI −12.09 to 3.65). Conclusions: Eight weeks of exercise training or lifestyle education can improve neuropathic signs and symptoms in people with diabetes and peripheral neuropathy. These findings support a role for lifestyle interventions in the management of peripheral neuropathy.